IMPLIKASI TRADISI PATTIDANA TERHADAP KEMATANGAN BERAGAMA UMAT BUDDHA THERAVADA DI VIHARA MENDUT, KOTA MUNGKID, MAGELANG, JAWA TENGAH - Alvista Fitri Ningsih (UIN Sunan Kalijaga Yogyakarta, 2017)
This writing provides us with an understanding of Pattidana tradition is something tradition for people Buddhist especially Theravada Buddhist to ancestors in nature with do something deeds virtue so that could lighten up load their suffering. This Pattidana tradition not be somethng transfer virtue however as try concentrate mind that initially difficult do virtue be could do virtue. With way often do Pattidana tradition especially family that involved and feel happy to virtue that do then could helpful especially for ancestors in nature. This Pattidana tradition be taught The Buddha and until while this still do by people Theravada Buddhist.